Covalent docking using autodock: Two‐point attractor and flexible side chain methods. (7th July 2015) - Bianco, Giulia; Forli, Stefano; Goodsell, David S.; Olson, Arthur J.
Abstract: We describe two methods of automated covalent docking using Autodock4: the two‐point attractor method and the flexible side chain method. Both methods were applied to a training set of 20 diverse protein–ligand covalent complexes, evaluating their reliability in predicting the crystallographic pose of the ligands. The flexible side chain method performed best, recovering the pose in 75% of cases, with failures for the largest inhibitors tested. Both methods are freely available at the AutoDock website (http://autodock.scripps.edu ).